Estrous cycle and uterine weight of ovariectomized menopause female rat models after treatment with Leucaena leucocephala (Lam.) de Wit leaf extract - Wiratmini, Ngurah Intan; Sukmaningsih, Anak Agung Sagung Alit; Setyawati, Iriani (Folia Medica Indonesiana, 2024)
Highlights: 1. This study found that Leucaena leucocephala leaf ethanol extract has the ability to stimulate the growth of vaginal epithelial cells in ovariectomised rats. 2. Leucaena leucocephala leaf extract can be developed as a safe and cost-effective natural alternative for hormone replacement therapy in premenopausal women and livestock. Highlights: 1. This study found that Leucaena leucocephala leaf ethanol extract has the ability to stimulate the growth of vaginal epithelial cells in ovariectomised rats. 2. Leucaena leucocephala leaf extract can be developed as a safe and cost-effective natural alternative for hormone replacement therapy in premenopausal women and livestock. Abstract Hormone replacement therapy has adverse effects that may cause additional health problems, such as hot flashes, cancer, ischemic stroke, and death. Phytoestrogen is an alternative ingredient used for hormone replacement therapy with less risk. The Leucaena leucocephala (Lam.) de Wit plant is widely used as a medicinal ingredient and animal feed. This study aimed to determine the effect of Leucaena leucocephala leaf extract on the uterine weight and estrous cycle of ovariectomized rats. This research used a completely randomized control design, which included two treatment groups (P1 and P2) and two control groups (negative (K-) and positive (K+)) with six replications in each group (n=24). The negative control (K-) was given 2 mL of corn oil, while K+ received 0.1 mg/kg bw of 17β-estradiol. P1 and P2 were administered 250 and 300 mg/kg bw of Leucaena leucocephala leaf extract, respectively. The extract was administered daily by gavage for 30 days. Estrous cycle data were obtained on day 31 by previously collecting vaginal swabs twice a day for 15 days. After the rats were sacrificed under anesthesia using chloroform, they underwent surgery to remove the uterine organs for weight measurement. The data were analyzed for normality and homogeneity using the Shapiro-Wilk and Levene tests. The data distribution were not normal, so the Kruskal Wallis test was used to test the hypothesis. If there was a difference between controls and treatments, the analysis continued with the Mann-Whitney test (p<0.05). The controls and treatments exhibited a significant difference in the length of each phase and overall estrous cycle. The post hoc Duncan test revealed that the highest uterine weight was found in 17β-estradiol treated rat. It was significantly different with both extracts treated rats. Both extract effect on uterine weight were not significantly difference. In conclusion, administering Leucaena leucocephala leaf extract results in an increased uterine weight and a normal estrous cycle in ovariectomized rats.